Pemberdayaan Masyarakat Dalam Pengelolaan Produk Olahan “Sambal Gurita Octonea” Dari Segi Kemasan Dan Kandungan Gizi Di Kecamatan Labuhan Haji, Kabupaten Lombok Timur - Mulyani, Laily Fitriani; Mukhlis, Alis; Dwiyanti, Septiana (Universitas Mataram, 2024)
One of the products of octopus biota that has been processed in the coastal area of ​​Labuhan Haji District, East Lombok Regency is octopus chili sauce made from octopus biota of the Octopus cyanea type or known as